Biochar Amendment and Nitrogen Fertilizer Contribute to the Changes in Soil Properties and Microbial Communities in a Paddy Field - Ali, Izhar; Yuan, Pengli; Ullah, Saif; Iqbal, Anas; Zhao, Quan; Liang, He; Khan, Abdullah; Imran; Zhang, Hua; Wu, Xiaoyan; Wei, Shanqing; Gu, Minghua; et al. (Frontiers in Microbiology, 2022)
Biochar amendment can influence the abundance, activity, and community structure of soil microbes. However, the effects of the combined application of biochar with synthetic N fertilizer under paddy field condition are little unknown or little information is available. In this study, we evaluated the consequences of different biochar rates in aggregate with extraordinary nitrogen fertilizers on soil nutrients, soil microbial abundance and rice grain yield in the course of 2019-2020. Eight treatments i.e., T1=0 t B ha-1+ N135 kg ha1, T2= 0 t B ha-1+ N180 kg ha1, T3= 10 t B + N135 kg ha 1, T4= 20 t B + N135 kg ha-1, T5= 30 t B + N135 kg ha1, T6= 10 t B + N180 kg ha1, T7= 20 t B + N180 kg ha 1 and T8= 30 t B + N360 kg ha-1 were used in this study. The soil microbial communities were characterized using high-throughput sequencing of 16S ribosomal RNA gene amplicons. Experiential findings showed that the treatments had biochar amendments along with nitrogen fertilizer significantly advanced soil pH, SOC, TN, SMBC, SMBN and rice grain yield in comparison to sole N application. Furthermore, in comparison with control in year 1 (2019), biochar amendment mixed with N fertilizer had a more desirable relative abundance of microorganisms, phyla Actinobacteria, Proteobacteria and Verrucomicrobia with better relative abundance ranging from 133. 56%, 26. 74% and 26. 38% in T7 respectively. Similarly, during 2020 bacteria phyla Acidobacteria, Actinobacteria, Bacteroidetes, Gemmatimonadetes, Planctomycetes and Verrucomicrobia were resulted in higher and ranging from 12.4%, 7.15%, 99.41%, 62.7%, 74.92% and 20.6%, in biochar applied treatments respectively as compared to control (T1). Interestingly biochar addition significantly decreased the soil fungi phyla Ascomycota, Basidiomycota, Chytridiomycota and Rozellomycota, in 2020 as compared to 2019. The redundancy analysis and Pearson correlation showed that soil biochemical traits were positively correlated with soil bacteria. Soil bacteria including Acidobacteria, Actinobacteria, Bacteroidetes, Planctomycetes, and Proteobacteria strongly correlated with rice grain yield. This study demonstrated that soil nutrients and bacteria contribute to an increase in rice yield in combined biochar amendment with lower nitrogen treatments.